Characterization and expression of macrophage migration inhibitory factor (mif) in Chinese sturgeon (Acipenser sinensis). Issue 103 (August 2020) - Jiang, Nan; Ni, Qi; Fan, Yuding; Wu, Shuwang; Zhou, Yong; Liu, Wenzhi; Si, Kaige; Zhang, Haigeng; Robert, Jacques; Zeng, Lingbing
Abstract: The Chinese sturgeon ( Acipenser sinensis ) is one of the critically endangered aquatic species in China. It is also among the oldest extant actinopterygian fish species. To advance the characterization of the Chinese sturgeon immune system, we identified the gene encoding the macrophage migration inhibitory factor (MIF), a multifunctional cytokine that contributes to both innate and adaptive immune responses. Molecular and phylogenic analysis indicates the Chinese sturgeon (cs) MIF share a high degree of structural conservation with other MIF sequences and is closely related to other bony fish MIF. At steady state, cs - mif gene is expressed at relatively high levels in the brain, and to a lesser but significant level in liver, spleen, kidney, gut and skin. The spatial expression patterns determined by in situ hybridization indicates a preferential distribution of cs-mif transcripts in the cerebral cortex, the gut epithelium, hematopoietic tissues of kidney, spleen and liver parenchyma, and skin epidermis. Marked increase of cs-mif gene expression was induced by lipopolysaccharide (LPS) stimulation and Aeromonas hydrophila infection in all tested tissues. Furthermore, higher cs-mif transcript levels were detected in the liver, spleen, kidney, gut and skin during stress response resulting from hyperthermia. These results are not only consistent with the expected role of cs- mif gene in innate immunity but also suggest a potential role of this gene in stress response to hyperthermia in the Chinese sturgeon. Highlights: Characterization of Chinese sturgeon mif gene and expression patterns. Higher cs-mif transcript levels were induced by bacterial, LPS and hyperthermia. A potential role of cs-mif in stress response to hyperthermia.